Model of Strengthening the Pedagogic Competence of Islamic Religious Education Teachers in Improving the Quality of Education in Junior High Schools in Jember Regency - Muhith, Abd. (Jurnal Pendidikan Agama Islam, 2021)
Teacher competence is one of the supporters of the successful implementation of education. The purpose of this study will be to explain the competency strengthening model for Islamic religious education teachers carried out by junior high schools in Jember Regency. This research is a qualitative research with a narrative approach. The main data sources in this study consisted of school principals and teachers in the district of Jember totaling 10 people consisting of Islamic religious education teachers and school principals. The selection of participants used purposive sampling technique. Data collection techniques were carried out by in-depth interviews and observations. The analytical technique used in processing the data is by reducing the data, presenting the results and interpreting the data. The results showed that there were three models of strengthening teachers' pedagogic competencies. First, training to equip and strengthen the knowledge, skills and attitudes of teachers in teaching. Second, mentoring is carried out to direct teachers in strengthening skills. Third, the supervision carried out by the principal to measure and provide an assessment of the competence of teachers who have been trained and assisted. The research that has been produced is expected to be the basis for making policies on strengthening competence for teachers in the future. Subsequent more in-depth research is very helpful in adding information about similar research.